Diagnosis of Cylindrocarpon destructans Using Enzyme-Linked Immunosorbent Assay - Taiying Li; Sungyeon Ji; Boknam Jung; Bo Yeon Kim; Kwang Sik Lee; Mun Won Seo; Sung Woo Lee; Jungkwan Lee; Seung-Ho Lee (Research in Plant Disease, 2019)
Cylindrocarpon destructans causes ginseng root rot and produces radicicol that has an antifungal effect. In this study, we developed a method to detect this fungus using enzyme-linked immunosorbent assay (ELISA). Secreted proteins of C. destructans were used as antigens to obtain C. destructans-specific IgG from mouse. Out of 318 monoclonal antibodies generated from mouse, two antibodies (Cd7-2-2 and Cd7-2-10) showed highest specificity and sensitivity. Indirect ELISA using both antigens successfully detected C. destructans in soils, but direct ELISA using IgG conjugated with horseradish peroxidase failed to detect antigens in soils. The indirect ELISA developed here can efficiently detect the fungus and help manage ginseng root rot disease in fields.